2014
DOI: 10.1002/stem.1619
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic Reprogramming of Patient-Derived Adipose Stem Cells by Prostate Cancer Cell-Associated Exosomes

Abstract: Emerging evidence suggests that mesenchymal stem cells (MSCs) are often recruited to tumor sites but their functional significance in tumor growth and disease progression remains elusive. Herein we report that prostate cancer (PC) cell microenvironment subverts PC patient adipose-derived stem cells (pASCs) to undergo neoplastic transformation. Unlike normal ASCs, the pASCs primed with PC cell conditioned media (CM) formed prostate-like neoplastic lesions in vivo and reproduced aggressive tumors in secondary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
202
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(221 citation statements)
references
References 54 publications
4
202
0
1
Order By: Relevance
“…Cancer cell-derived exosomes have been implicated in determining the tumorigenic potential of epithelial cells (14,21,84,85). Cancer exosome miR may also contribute to tumorigenesis, and cancer exosomes can mediate cell-independent miR biogenesis, a property not associated with normal exosomes.…”
Section: Function Of Exosomes In Cancer Therapiesmentioning
confidence: 99%
“…Cancer cell-derived exosomes have been implicated in determining the tumorigenic potential of epithelial cells (14,21,84,85). Cancer exosome miR may also contribute to tumorigenesis, and cancer exosomes can mediate cell-independent miR biogenesis, a property not associated with normal exosomes.…”
Section: Function Of Exosomes In Cancer Therapiesmentioning
confidence: 99%
“…It has been suggested that stress, including hypoxia in the TME, accounts for this copious TEX secretion by tumor cells (36). TEX production and release by tumor cells was also reported to be regulated by p53 (37).…”
Section: Functional Attributes Of Texmentioning
confidence: 99%
“…The qPCR and miRNA analyses were performed as previously described (20,21). Analysis details and primers used for gene expression (Supplementary Table S2) and miRNAs (Supplementary Table S3) are provided in the Supplementary Methods.…”
Section: Quantitative Pcr and Mirna Analysismentioning
confidence: 99%
“…The assays were performed as previously described (21). Experimental details are furnished in Supplementary Information.…”
Section: Immunoblot Co-immunoprecipitation and Reporter Assaysmentioning
confidence: 99%